Perbedaan atherogenic index of plasma, ox-LDL dan troponin I pada pasien penyakit jantung koroner stabil dan sindrom koroner akut - Eti Dwi Purwati; Purwanto Adhipireno; Muji Rahayu (Intisari Sains Medis, 2020)
Background: Coronary heart disease (CHD) is caused by atherosclerosis in the coronary arteries. Lipid lipoprotein abnormalities as the pathogenesis basic of atherosclerosis can be assessed using atherogenic index of plasma (AIP) and oxidized low density lipoprotein level (ox-LDL). Troponin I has a role in heart muscle damage due to ischemia in CHD. This study aimed to determine the differences of AIP, ox-LDL and troponin I levels in patients with stabel CHD and acute coronary syndrome (ACS).Methods: This is an observational analytic study with cross-sectional including 34 stable CHD patients and 34 ACS patients from January to March 2019 at Kariadi hospital Semarang. Measurement of triglycerides (TG) and HDL using automatic chemistry, AIP is calculated from log TG/HDL, ox-LDL levels using the ELISA method, troponin I using the ELFA method. AIP statistical analysis used independent t-test while ox-LDL and troponin I levels statistical analysis was using Mann whitney U test. Significant difference was determiner when p < 0.05.Results: Mean ± SD of AIP in stable CHD was 0.52 ±  0.25 and ACS was 0.55 ± 0.23 with  p = 0.622. Median (min-max) of ox-LDL in stable CHD was 324.74 pg/ml (67.44 – 891.98) and ACS was 717.18 pg/ml (87.35 – 1959.4) with p £ 0.001 and median (min – max) troponin I in stable CHD was 0.026 ug/L (0.018 – 0.035) and ACS was 1.5 ug/L (0.003 – 40) with p £ 0.001.Conclusion: There were significant differences in ox-LDL and troponin I levels between stable CHD and ACS. There was no significant differences ofAIP show in stable CHD patients and ACS. Pendahuluan: Penyakit jantung koroner (PJK) disebabkan aterosklerosis pada arteri koroner. Kelainan lipid lipoprotein yang menjadi dasar patogenesis aterosklerosis dapat dinilai dengan atherogenic index of plasma (AIP), oxidized low density lipoprotein (ox-LDL). Troponin I berperan pada kerusakan otot jantung akibat iskemia pada PJK. Tujuan dari penelitian ini adalah untuk membuktikan perbedaan nilai AIP, kadar ox-LDL dan troponin I pada pasien PJK stabil dan sindrom koroner akut (SKA).Metode: Penelitian observasional analitik dengan pendekatan potong lintang dilakukan pada 34 pasien PJK stabil dan 34 pasien SKA di RSUP Dr. Kariadi Semarang. Penetapan trigliserida (TG) dan HDL menggunakan kimia otomatik, AIP dihitung dari log TG/HDL, kadar ox-LDL menggunakan metode ELISA, troponin I mengunakan metode ELFA. Analisis statistik AIP menggunakan independent t-test sedangkan kadar ox-LDL dan troponin I menggunakan Mann whitney U test. Perbedaan bermakna apabila p < 0.05.Hasil: Rerata ± SD nilai AIP PJK stabil adalah 0.52 ± 0.25 dan SKA 0.55 ± 0.23 dengan p = 0.622. Median (min – maks) ox-LDL PJK stabil 324.74 (67.44 – 891.98) pg/ml dan SKA 717.18 (87.35 – 1959.4) pg/ml dengan nilai p £ 0.001, dan median (min – maks) troponin I PJK stabil 0.026 (0.018 – 0.035) ug/L dan SKA 1.5 (0.003 – 40) ug/L dengan nilai p £ 0.001.Simpulan: Terdapat perbedaan bermakna kadar ox-LDL dan troponin I dan perbedaan tidak bermakna nilai AIP pada pasien PJK stabil dan SKA.